Investigating the relationship between reservoir properties and sedimentary processes in the Ilam Formation of Susangerd oilfield, SW Iran - Razieh Fouladvand; Mohammadhossein Adabi; Abas Sadeghi; Mahmoud Jalali (Journal of Stratigraphy and Sedimentology Researches, 2022)
Abstract To developing and explore hydrocarbon fields, it is necessary to know geological models and reservoir quality changes. Therefore, the Ilam Formation with approximate 145m thickness was examined in the Susangerd oilfield. The sedimentary model was considered carbonate ramp type due to the lack of slump and reef structures. Two complete and one incomplete third-order sedimentary sequences were identified. Close to the sequence boundary in the middle part of the Ilam Formation, reservoir conditions improve with the development of vug and mold dissolutions, especially in green algae by corrosive fluids passing through stylolites and fractures. But near the sequence boundary in the upper part of the Ilam Formation, however intergranular porosity develops between peloids and ooids but almost destroyed with cementation. The southeastern domain of the oilfield contains shallower microfacies in the lower sedimentary sequence and most part of transgressive system tract of the middle sequence in comparison with the northwestern domain. It seems that the southeastern part of the oilfield is located on paleo high and the lower values ​​of porosity log in the northwestern part are probably due to the distance from this paleo high. Therefore, the southeast of the oilfield is suggested for the development of the Susangerd oilfield and future explorations. Keywords: Sedimentary environment, Sedimentary sequence, Reservoir quality, Ilam Formation, Susangerd oilfield